HYDROCARBON POTENTIAL IN JORDAN. (19th June 2013) - Naylor, D.; Al‐Rawi, M.; Clayton, G.; Fitzpatrick, M. J.; Green, P. F.
<x xml:space="preserve">Abstract</x> The paper presents results from a range of petroleum exploration studies carried out in Jordan – some regional in approach, others focussed on the NE of the country – together with a review of existing literature and industry reports. The dominant active structural feature in Jordan is the NNW‐SSE striking Dead Sea Transform, characterised in southern Jordan by extensional splay fault arrays, pull‐apart basins and relay‐sag basins. Elsewhere in the country there are regional‐scale strike‐slip faults (ENE‐WSW, NNW‐SSE) with multiple phases of reactivation. Stratigraphic studies have identified potential reservoir intervals within the Lower Palaeozoic Salib, Umm Sahm, Disi and upper Dubaydib (Risha Sandstone Member) Formations, and also within the Triassic and Cretaceous intervals. Potential source rocks occur within the Lower Palaeozoic Burj, lower Hiswa and Dubaydib Formations and at basal and Upper Silurian levels, with limited additional potential in the Triassic and possibly Permian successions. Apatite fission track analysis (AFTA), zircon fission track analysis (ZFTA) and vitrinite reflectance (VR) studies of selected wells and outcrop samples indicate that the thermal history of eastern Jordan is dominated by the effects of two major periods of relatively deep burial, with subsequent exhumation phases beginning in the Late Palaeozoic and Late Cenozoic. An intermediate episode (Mesozoic) of deep burial and exhumation is possible. Significant variations in heat flow regimes and burial patterns occur in different parts of Jordan, probably controlled by deep structure and burial history. Over much of the north of the country, the Lower Palaeozoic succession is in the gas window and the underlying section is overmature. The main hydrocarbon generation and expulsion phase in this region was in the Late Palaeozoic and was terminated by "Hercynian" (Late Palaeozoic) uplift. Further south, the Silurian and Upper Ordovician sections are in the oil window, and deeper source intervals are mature for gas. The Triassic interval is a valid hydrocarbon play in the NW and NE of Jordan, with oil sourced from either Permian, Triassic or Cretaceous kitchens. Upper Cretaceous source rocks within the thicker Mesozoic sections in the Azraq Graben are in the oil window and have sourced the small‐scale Hamza oilfield. In addition to the known widespread Upper Cretaceous – Paleocene oil shale potential in Jordan, the Ordovician and Silurian sections have potential for shale gas in northern Jordan and for shale oil further south.